Development of E-Comic Media on the Human Digestive System to Improve Learning Outcomes of Grade V Primary School Students - Aprilia Diva Anggarawati; Albertus Hartana (Universitas Pendidikan Ganesha, 2026)
Technological developments in today's world of education are rapid and innovative, as is the use of learning media by educators in the development of education in the digital age. This study aims to develop e-comic media on the human digestive system to improve the learning outcomes of fifth-grade primary school students. This study uses the Research and Development (R&D) method with the ADDIE model: Analyse, Design, Develop, Implement, Evaluate. The subjects of this study involved subject matter experts, media experts, two fifth-grade teachers, and 22 fifth-grade students State Elementary School. Data collection was conducted using analysis questionnaires and interviews with fifth-grade teachers. Data analysis was performed using qualitative and quantitative techniques. The results showed that 1) the development of e-comic media for fifth-grade elementary school students on the human digestive system was carried out by following the ADDIE stages: Analyse, Design, Develop, Implement, Evaluate. 2) The quality of the e-comic media was assessed by subject matter experts, media experts, and fifth-grade teachers as very good and suitable for testing according to the experts' suggestions. The application of e-comic learning media had an effect on student learning outcomes, with an increase from pretest scores to posttest scores, representing a 54% increase in learning outcomes. Thus, it can be concluded that e-comic media for fifth-grade elementary school students on the human digestive system can improve learning outcomes and is suitable for use in continuous learning.